Utility of magnetic resonance imaging of brain in neurocritically ill children in pediatric intensive care unit: A single-center retrospective observational study - Uroosa Saman; Anwarul Haque; Namaya Hussain; Bushra Shamim (Wolters Kluwer Medknow Publications, 2024)
Background: Brain magnetic resonance imaging (MRI) was increasingly performed in children admitted in pediatric intensive care unit (PICU) with acute nontraumatic neurological disorders. The study aimed to describe neuroimaging findings and contribution of brain MRI in children admitted with acute encephalopathy admitted in PICU as well as adverse events during procedure. Subjects and Methods: Retrospective chart of all children with nontraumatic acute brain insults required MRI of brain admitted in PICU from January 2019 to December 2021. Demographic, clinical diagnosis, ICU therapies, and pertinent neurodiagnostic data were collected into a structured data collection sheet. The neurodiagnostic findings, contribution in the clinical management either as diagnostic, therapeutic, or prognostic as well as any adverse events during procedure and transport were also collected. All transport and procedure was done by pediatric intensive care team. Appropriate descriptive and analytical statistical tests were applied. Results: Eight two had brain MRI during the study period. The median age (year) was 3.0 (2 mo.-16 years) the most common admitting diagnoses were central nervous system infections in 39 (47.5%) and Status epilepticus in 7 (8%) cases. Neurodiagnostic categories of MRI were inflammatory in 34 (41.5%) and vascular/ischemia in 23 (28%) cases. Brain MRI was contributory in 57 (69.5%) cases in management of child as diagnostic in 41 (71.9%), prognostic in 15 (26%) therapeutic in 1 (1.7%) while noncontributory in 25 (30%) cases. No adverse events were reported during MRI. Conclusions: Brain MRI was helpful for the diagnosis as well as prognosis for acute neurocritically ill children in PICU and associated with very few minor adverse events.